Economic policy: an alternative proposal - Palacios, Eduardo Sarmiento (Universidad Pedagógica y Tecnológica de Colombia, 2001)
The author examines the economic opening, its principles and basis. He claims that this policy was implemented by the Issuing Bank (Central Bank) which main policies were designed from the Agreement of Washington. It is stated that the result of these policies in terms of economic growth, employment, income, etc. are poor. That is why there the need to propose a new model aimed at improving productivity, and employment, but especially equal opportunities for everybody